The nature of peer‐directed behaviours in children with profound intellectual and multiple disabilities and its relationship with social scaffolding behaviours of the direct support worker. (22nd October 2015) - Nijs, S.; Vlaskamp, C.; Maes, B.
Abstract: Background: The multiple and complex disabilities of persons with profound intellectual and multiple disabilities (PIMD) form a barrier for peer interactions and peer‐directed behaviours. In this study, we further explore the nature of peer‐directed behaviours in persons with PIMD and its relationship with social scaffolding behaviour of direct support workers (DSWs). Methods: Fourteen dyads of children with PIMD, who knew each other for at least 12 months, participated. They were sitting in close proximity while they were filmed with and without the presence of the DSW. Video recordings were coded continuously making use of observation schemes for the peer‐directed behaviours of the children and the peer interaction influencing behaviours of the DSW. Results: Significantly more singular peer‐directed behaviour (without DSW: 18.00%; with DSW: 3.81%) was observed than multiple peer‐directed behaviour (without DSW: 4.01%; with DSW: 0.52%). The amount of time the singular and multiple peer‐directed behaviours were observed was significantly lower in the presence of a DSW. When the DSW shows peer interaction influencing behaviour, it was mostly social scaffolding behaviour (2.17%). The conditional probability of observing social scaffolding behaviour in the 10 s following on singular peer‐directed behaviour was 0.02 with a Yule's Q of 0.04 and following on multiple peer‐directed behaviour 0.04 with a Yule's Q of 0.33. Conclusion: The way in which peer interactions in children with PIMD are defined could have an impact on the amount of observed peer‐directed behaviours and on the effect of the social scaffolding behaviours presented by DSW.